Magic Hour - Isaacs, Susan (New York Harper Paperbacks, 1997)
As Steve Brady investigates Bonnie, the ex-wife of the murder victim and the probable culprit, he also falls in love with her as he ignores "all the rules, all the evidence, and all common sense"--Cover.
Keywords: Detective and mystery stories -- Murder--Investigation